Penerapan Kurikulum 2013 di Madrasah Ibtidaiyah Walisongo Kranji 01 Pekalongan - Mulyani, Tri; Kartikawati, Adhisa; Fadhilah, Maulida Nur; Annur, Aan Fadia (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2022)
The curriculum is the totality of activities designed by schools to provide various experiences for students, both inside and outside the classroom. The curriculum is not only synonymous with subject matter, but all activities designed by schools to develop students' self-capacity are also included in the curriculum. Education is a human process that must be developed according to human needs. Human needs always develop all the time along with the rapidly changing times. Madrasah Ibtidaiyah (MI) 01 Kranji is an Islamic educational institution that is sensitive to the special needs of the surrounding community. This institution responds to community needs by developing a leadership curriculum. The curriculum is an answer to the needs of people who are concerned about the condition of youth who do not have leadership characteristics such as responsibility, discipline, courage, honesty and cooperation. This study seeks to reveal the curriculum model that was applied and developed by MI Walisongo 01 Kranji. The research method that the author uses is descriptive qualitative using data collection techniques, interviews, documentation, and observation.